TAFE accounting : basic reports - Mroczkowski, Nicholas A.; Yates, Lindsay; Fleay, Daryl (Melbourne VIC : Nelson, 1995)
This book is about: Accounting standards; Accounting for fixed assets; balance-day adjustments and closing entries; Final reports; ...
Keywords: Accounting; Accounting; Bookkeeping